Prognosis of invasive encapsulated follicular variant and classical papillary thyroid carcinoma: a propensity score-matched study using the SEER database - Shuai Jin; Lang Xie; Gongyou Zhang; Lei Liu; Kaide Xia; Hongzhou Liu; Haiwang Zhang; Peng Li (Scientific Reports)
Abstract The latest World Health Organization Classification of Tumors, Fifth Edition, recognizes the invasive encapsulated follicular variant of papillary thyroid carcinoma (IEFVPTC) as a distinct malignant entity rather than a subtype of papillary thyroid carcinoma (PTC). This reclassification highlights the need to explore potential prognostic differences between IEFVPTC and classic PTC. This study utilized the Surveillance, Epidemiology, and End Results (SEER) database to compare prognoses of patients diagnosed with IEFVPTC and classic PTC between 2004 and 2019. Propensity score matching (PSM) was employed to adjust for confounding variables and reduce selection bias. Kaplan-Meier survival curves and Cox regression models were used to evaluate overall survival (OS) between the two groups. A total of 1,530 IEFVPTC and 81,508 classic PTC patients were analyzed. Before PSM, significant differences were noted in race, T-stage, N-stage, M-stage, laterality, radiotherapy, surgical modality, tumor size, and income. Post-PSM, these differences were not statistically significant (p > 0.05). Kaplan-Meier curves and Cox regression models showed no significant differences in OS between IEFVPTC and classic PTC both before and after PSM. This PSM analysis revealed no significant differences in overall survival between patients with IEFVPTC and classic PTC, suggesting that the reclassification of IEFVPTC does not translate into distinct prognostic outcomes.